Naked deltahedral silicon clusters in solution: synthesis and characterization of Si9(3-) and Si5(2-). - Goicoechea, J; Sevov, S (2004)
Elusive for over 100 years, deltahedral Zintl ions of silicon are finally synthesized and structurally characterized. The two clusters reported here, Si93- and Si52-, are analogous to known clusters of the heavier members of this group: Ge, Sn, and Pb.